66 Quetiapine Induced Dress Syndrome - Vishal R. Tandon; Roshi; Poonam Sharma; Annil Mahajan (Dr. Annil Mahajan, 2022)
Quetiapine is second-generation antipsychotic drug used in conditions like affective disorders, anxiety disorders, autism, spectrum disorders, dementia and delirium. Anticonvulsants like phenytoin, phenobarbitone, carbamazepine, sulphonamides and allopurinol are the most common drugs responsible for developing DRESS syndrome. We failed to cite any case of DRESS syndrome caused by quetiapine while reviewing the literature. Hence we, report possibly a first case of DRESS syndrome caused by quetiapine.